Efficacy of bacterial ribosomal RNA-targeted reverse transcription-quantitative PCR for detecting neonatal sepsis: a case control study - Sato Hiroaki; Shoji Hiromichi; Komatsu Mitsutaka; Matsunaga Nobuaki; Nagata Satoru; Hisata Ken; Fujimori Makoto; Yamashiro Yuichiro; Asahara Takashi; Nomoto Koji; Shimizu Toshiaki (BMC, 2010)
Abstract Background Neonatal sepsis is difficult to diagnose and pathogens cannot be detected from blood cultures in many cases. Development of a rapid and accurate method for detecting pathogens is thus essential. The main purpose of this study was to identify etiological agents in clinically diagnosed neonatal sepsis using bacterial ribosomal RNA-targeted reverse transcription-quantitative PCR (BrRNA-RT-qPCR) and to conduct comparisons with the results of conventional blood culture. Since BrRNA-RT-qPCR targets bacterial ribosomal RNA, detection rates using this approach may exceed those using conventional PCR. Methods Subjects comprised 36 patients with 39 episodes of suspected neonatal sepsis who underwent BrRNA-RT-qPCR and conventional blood culture to diagnose sepsis. Blood samples were collected aseptically for BrRNA-RT-qPCR and blood culture at the time of initial sepsis evaluation by arterial puncture. BrRNA-RT-qPCR and blood culture were undertaken using identical blood samples, and BrRNA-RT-qPCR was performed using 12 primer sets. Results Positive rate was significantly higher for BrRNA-RT-qPCR (15/39, 38.5%) than for blood culture (6/39, 15.4%; p = 0.0039). BrRNA-RT-qPCR was able to identify all pathogens detected by blood culture. Furthermore, this method detected pathogens from neonates with clinical sepsis in whom pathogens was not detected by culture methods. Conclusions This RT-PCR technique is useful for sensitive detection of pathogens causing neonatal sepsis, even in cases with negative results by blood culture.